Toxoplasma gondii e Neospora caninum em cães provenientes de Tocantins: Sorologia e fatores associados - Raimundo, Juliana Macedo; Guimarães, Andresa; Moraes, Larissa Martins de Brito; Santos, Lucélia Azevedo; Nepomuceno, Leandro Lopes; Barbosa, Silvia Minharro; Pires, Marcus Sandes; Santos, Huarrisson Azevedo; Massard, Carlos Luiz; Machado, Rosangela Zacarias [UNESP]; Baldani, Cristiane Divan (FapUNIFESP (SciELO), 2015)
This study investigated occurrences of anti-Neospora caninum and anti-Toxoplasma gondii IgG antibodies by means of the enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescence assay (IFAT), along with risk factors associated with toxoplasmosis and neosporosis, in 204 dogs from urban and rural areas of the municipality of Araguaína, state of Tocantins, Brazil. One hundred and thirty samples (63.7%) were positive for T. gondii using ELISA: 57.1% and 70.7% in the urban and rural areas, respectively. The seropositivity frequency for T. gondii observed through IFAT was 57.4%, distributed between rural and urban areas as 62.6% and 52.4%, respectively. The factors associated with canine toxoplasmosis were age and breed (p<0.05). In relation to N. caninum, 88 samples (43.1%) were positive, according to ELISA, distributed as 42.9% in urban areas and 43.3% in rural areas. Anti - N. caninum antibodies were detected through IFAT in 62 dogs (30.4%), distributed as 31.3% and 29.5% between rural and urban areas, respectively. Age and breed were associated with neosporosis occurrence (p<0.05) by IFAT. This study provides the first detection of IgG antibodies for canine toxoplasmosis and neosporosis in the state of Tocantins and highlights the importance of dogs in the epidemiological chain of these diseases.
Toxoplasma gondii and Neospora caninum in dogs from the state of Tocantins: Serology and associated factors
Keywords: Dogs; ELISA; IFAT; Neosporosis; Toxoplasmosis